Safety and efficacy of the use of lumen-apposing metal stents in the management of postoperative fluid collections: a large, international, multicenter study - Yang, Juliana; Kaplan, Jeremy H.; Sethi, Amrita; Dawod, Enad; Sharaiha, Reem Z.; Chiang, Austin; Kowalski, Thomas; Nieto, Jose; Law, Ryan; Hammad, Hazem; Wani, Sachin; Wagh, Mihir S.; Yang, Dennis; Draganov, Peter V.; Messallam, Ahmed; Cai, Qiang; Kushnir, Vladimir; Cosgrove, Natalie; Ahmed, Ali Mir; Anderloni, Andrea; Adler, Douglas G.; Kumta, Nikhil A.; Nagula, Satish; Vleggaar, Frank P.; Irani, Shayan; Robles-Medranda, Carlos; El Chafic, Abdul Hamid; Pawa, Rishi; Brewer, Olaya; Sanaei, Omid; Dbouk, Mohamad; Singh, Vikesh K.; Kumbhari, Vivek; Khashab, Mouen A. (Endoscopy, 2019)
Background Multiple studies have examined the use of lumen-apposing metal stents (LAMSs) for the drainage of peripancreatic fluid collections. Data on the use of LAMSs for postoperative fluid collections (POFCs) are scarce. POFCs may lead to severe complications without appropriate treatment. We aimed to study the outcomes (technical success, clinical success, rate/severity of adverse events, length of stay, recurrence) of the use of LAMSs for the drainage of POFCs. Methods This international, multicenter, retrospective study involved 19 centers between January 2012 and October 2017. The primary outcome was clinical success. Secondary outcomes included technical success and rate/severity of adverse events using the ASGE lexicon. Results A total of 62 patients were included during the study period. The most common etiology of the POFCs was distal pancreatectomy (46.8 %). The mean (standard deviation) diameter was 84.5 mm (30.7 mm). The most common indication for drainage was infection (48.4 %) and transgastric drainage was the most common approach (82.3 %). Technical success was achieved in 60/62 patients (96.8 %) and clinical success in 57/62 patients (91.9 %) during a median (interquartile range) follow-up of 231 days (90 – 300 days). Percutaneous drainage was needed in 8.1 % of patients. Adverse events occurred intraoperatively in 1/62 patients (1.6 %) and postoperatively in 7/62 (11.3 %). There was no procedure-related mortality. Conclusion This is the largest study on the use of LAMSs for POFCs. It suggests good clinical efficacy and safety of this approach. The use of LAMSs in the management of POFCs is a feasible alternative to percutaneous and surgical drainage.